Therapeutic efficacy of β-sitosterol treatment on Trypanosoma congolense infection, anemia development, and trans-sialidase (TconTS1) gene expression - Aminu, Suleiman; Chechet, Gloria Dada; Alkhalil, Samia S.; Sobeh, Mansour; Daoud, Rachid; Simelane, Mthokozisi B.; Onyike, Elewechi; Ibrahim, Mohammed Auwal (Frontiers in Microbiology, 2023)
Background: African animal trypanosomiasis hinders sustainable livestock productivity in sub-Saharan Africa. About 17 million infected cattle are treated with trypanocides annually but most of the drugs are associated with drawbacks, necessitating the search for a promising chemotherapeutic agent. Objectives: In this study, the effects of β-sitosterol on Trypanosoma congolense infection were investigated along with its effect on the trans-sialidase gene expressions. Results: Oral treatment with β-sitosterol at 15 and 30 mg/kg body weight (BW) for 14 days significantly (P < 0.05) reduced parasitemia and ameliorated the parasite-induced anemia. Also, the parasite-induced increase in serum urea level and hepatic and renal histopathological damage scores in addition to renal hypertrophy was significantly (P < 0.05) reverted following treatment with 30 mg/kg BW β-sitosterol. The compound also significantly (P < 0.05) down-regulated the expression of TconTS1 but not TconTS2, TconTS3, and TconTS4. Correlation analysis between free serum sialic acid with the TconTS1 and TconTS2 gene variants revealed negative correlations in the β-sitosterol-treated groups although they were non-significant (P > 0.05) in the group treated with 15 mg/kg BW β-sitosterol. Similarly, a non-significant negative (P > 0.05) correlation between the biomolecule and the TconTS3 and TconTS4 gene variants was observed in the β-sitosterol-treated groups while positive correlations were observed in the infected untreated control group. Conclusions: The observed effect of β-sitosterol on T. congolense infection could make the compound a possible template for the design of novel trypanocides.